PROBLEMATIKA GURU DALAM MENGIMPLEMENTASIKAN KURIKULUM MERDEKA PADA MAPEL AKIDAH AKHLAK DI MTS NEGERI 3 SLEMAN - Rubiatul Aslamiyah; Muh. Wasith Achadi (Raudhah - Proud To Be Professional, 2024)
The independent curriculum is the latest curriculum designed to give freedom to schools and teachers in designing learning to be fun and tailored to student interests. This study aims to analyze the problems of teachers in implementing the independent curriculum in the subject of moral creed at MTs Negeri 3 Sleman. This research is a qualitative research with descriptive method. The informants in this study were moral creed teachers at MTs Negeri 3 Sleman. Data collection techniques using observation, interviews, and documentation. The results showed that there were 3 probelamatika faced by moral creed teachers at MTs Negeri 3 Sleman in implementing the independent curriculum, namely: 1) Low student motivation, 2) Teacher readiness in implementing an independent curriculum, 3) Challenges in developing teaching materials. In dealing with these problems, there are two solutions offered by the moral creed teacher, namely: 1) Collaborating between various parties, 2) Improve teacher competence through training. The implications of this research can be used as a reference for schools or teachers to be able to design strategies and improvements to the problems faced in implementing the independent curriculum.